Helicobacter pylori regulates ILK to influence autophagy through Rac1 and RhoA signaling pathways in gastric epithelial cells. (September 2021) - Xu, Zheng; Li, Boqing; Du, Yunqiu; Zhang, Ruiqing; Tong, Xiaohan; Li, Jing; Wu, Yulong; Ji, Xiaofei; Zhang, Ying
Abstract: The ability of Helicobacter pylori to manipulate host autophagy is an important pathogenic mechanism. We found an inverse correlation between the expression of ILK and the autophagy marker protein LC3B in H. pylori -positive human samples, H. pylori -infected mice models and H. pylori- infected GES-1 cell lines. When the ILK-knockdown GES-1 cells were infected by H. pylori, CagA were significantly degraded, autophagosomes accumulation and autolysosomes formation were significantly increased, and LC3B protein levels and ratio of LC3BII to LC3BI were also remarkably upregulated. And chloroquine treatment increased LC3B levels in ILK-knockdown GES-1 cells. The expression levels of both Rac1 and RhoA were downregulated in GES-1 cells after H. pylori infection and were decreased in ILK-knockdown GES-1 cells. The mRNA and protein levels of PAK1, MLC, and LIMK were significantly decreased and cofilin mRNA and protein levels were significantly increased in GES-1 cells treated with the Rac1 inhibitor NSC 23766. The mRNA and protein levels of ROCK1, ROCK2, MLC, and LIMK1 were significantly reduced and cofilin mRNA and protein levels were significantly increased in GES-1 cells treated with the RhoA inhibitor CCG-1423. F-actin was significantly reduced in Rac1- or RhoA-inhibited GES-1 cells. F-actin depolymerization induced autophagosomes accumulation, autolysosomes formation, and the increase of LC3B levels in GES-1 cells. Therefore, these findings revealed that ILK could serve as a novel regulator to affect Rac1/PAK1 and RhoA/ROCKs signaling pathways, thereby influencing H. pylori -induced autophagy. Highlights: ILK was a critical regulator for H. pylori -induced autophagy. Rac1 and RhoA influenced autophagy in an ILK-dependent manner. H. pylori stabilized its chronic infection through ILK/Rac1/RhoA signaling pathway.